HUBUNGAN PANJANG, LINGKAR, DAN VOLUME SKROTUM DENGAN VIABILITAS DAN ABNORMALITAS SPERMATOZOA PADA KAMBING PEJANTAN PERANAKAN ETAWAH (PE) - Pangestu, Mukti Santoso Aji; Sumaryadi, Mas Yedi; Nugroho, Aras Prasetiyo (Fakultas Peternakan Universitas Jenderal Soedirman, 2021)
Background. The study of the relationship between Length, Circumference, and Volume of the scrotum with Viability and Abnormality of Spermatozoa in Etawa Crossbreed (PE). Goats was carried out from 15 November 2020 until 21 November 2020 at Tani Ternak Sato Guno, Gumelar District, Banyumas Regency, Central Java. Materials and methods. The purpose of this study was to determine the length, circumference, volume of the scrotum with the viability and abnormalities of spermatozoa in Etawa male goats, provide scientific information and expand knowledge in the field of animal husbandry, especially the quality of spermatozoa. This research uses experimental with linear correlation analysis method and linear regression analysis. Results. The results of this study indicate that together the length, circumference, and volume of the scrotum have a very strong relationship (P < 0.01) with spermatozoa viability with a coefficient of determination of 0.825 and a correlation coefficient of r = 0.908. This shows that the viability of spermatozoa is influenced by the length, circumference, and volume of the scrotum by 82.5%, while the remaining 17.5% is influenced by other factors. The results of the next study showed that together the length, circumference, and volume of the scrotum had a very strong relationship (P < 0.01) with spermatozoa abnormalities with a coefficient of determination of 0.918 and a correlation coefficient of r = 0.958. This shows that spermatozoa abnormalities are influenced by the length, circumference, and volume of the scrotum by 91.8%, while the remaining 8.2% are influenced by other factors. It was concluded that the mean length, circumference, and scrotum volume of Etawa Crossbreed Goats were 25.50 ± 1.73 cm, respectively; 15.00 ± 1.28 cm; 85.96 ± 20.39 cm3 with the mean viability and abnormality of spermatozoa were 82.12 ± 5.71% and 4.54 ± 2.35%, respectively. Conclusion. Length, circumference, and volume of the scrotum simultaneously have a very strong relationship with the viability and abnormality of spermatozoa, so that it can be used as a good indicator to estimate the quality of spermatozoa, especially the viability and abnormality of spermatozoa with the respective formulas being Y₁ + = 232,500 - 6,500 X₁ - 3,583 X₂ + 0.212 X₃ and Y₂ += 69,000 + 0.917 X₁ - 3.801 X₂ + 0.103 X₃